Mortality in malnourished older adults diagnosed by ESPEN and GLIM criteria in the SarcoPhAge study. Issue 5 (13th July 2020) - Sanchez‐Rodriguez, Dolores; Locquet, Médéa; Reginster, Jean‐Yves; Cavalier, Etienne; Bruyère, Olivier; Beaudart, Charlotte
Abstract: Background: The Global Leadership Initiative on Malnutrition (GLIM) criteria have been recently launched by consensus of the major nutrition societies. GLIM criteria are partly constructed on the previous definition of malnutrition developed by the European Society of Clinical Nutrition and Metabolism (ESPEN). We aimed to assess malnutrition according to the ESPEN and GLIM criteria at baseline and to determine the corresponding risk of mortality during a 4‐year follow‐up in community‐dwelling older adults from the SarcoPhAge ( Sarco penia and Ph ysical Impairment with advancing Age ) study. The relationship between malnutrition and incidence of 4‐year adverse health consequences (institutionalization, hospitalization, falls, and fractures) was assessed. Methods: This prospective population‐based cohort was part of SarcoPhAge, which included 534 older adults in Belgium, followed up from 2013 to 2019. Community‐dwelling healthy volunteers ≥65 years old were recruited. Mortality and adverse health consequences were collected annually by interview or phone call. Baseline malnutrition was defined according to the GLIM and ESPEN criteria. Agreement between the two definitions was reported by Cohen's kappa coefficient. Adjusted Cox regression and Kaplan–Meier survival curves were performed for malnutrition. Logistic regression was used for the other outcomes. Results: From 534 subjects in SarcoPhAge, the records for 411 participants (73.2 ± 6.05 years old; 55.7% women) had all the variables needed to apply the GLIM criteria. Prevalence of baseline malnutrition was 23.4% for GLIM and 7% for ESPEN criteria ( k = 0.30, low agreement). The adjusted Cox regression showed a significant increased mortality risk according to malnutrition status as defined by the GLIM [adjusted hazard ratio = 4.41 (95% confidence interval: 2.17–8.97)] and ESPEN [adjusted hazard ratio = 2.76 (95% confidence interval: 1.16–6.58)] criteria. Survival curves differed significantly between malnourished and non‐malnourished groups, regardless of the definition used (log rank P < 0.001 for both). No association was found between baseline malnutrition according to these two criteria and 4‐year risk of institutionalization, hospitalization, falls, or fractures (all P > 0.05). Conclusions: Malnutrition according to the GLIM criteria was associated with a 4.4‐fold higher mortality risk, double that of the ESPEN criteria, during a 4‐year follow‐up. No association was found between malnutrition according to these two criteria and incidence of other health adverse consequences. GLIM criteria anticipate mortality and might guide interventions, with important implications for clinical practice and research.